Determinasi Motivasi, Disiplin dan Kompensasi terhadap kinerja karyawan PT. Wika Lautan Teduh - Reza Safitri (STIA Indragiri, 2017)
ABSTRACTThe purpose of this research was for testing and analyzing determinant of motivation, disciplination, and compensation of employee performance in PT Wika Citra Lautan Teduh. Motivation and disciplination are such an important rule in performance value, and compensation has influence to employee performance, when higher compensation the employee could get, would be higher the performance they would give. Performance is comparation of output the employee could reached of the company’s standart.Testing data technique that used in this research includes validation test with factor analyze, reliability test with Cronbach Alpha. Classic asumtion test and multiple linear regression analyze for testing and proofing the hyphotesis of this research. Collecting data was using questionnaire, and analyzed by software SPSS version 21.The result of hyphotesis test for motivation, has positive influence to employee performance, with t test was 2,514, in significance by 0,013, means hyphotesis of this research was accepting Ha and rejecting Ho. Second hyphotesis of disciplination showed, it has influence to employee performance by -1,778 with significance level by 0.078 (Sig. 0.078 > 0.05) which means accepting Ho and rejecting Ha. Third hyphotesis showed that compensation has influence to employee performance.